2013
DOI: 10.1039/c3ay40995c
|View full text |Cite
|
Sign up to set email alerts
|

A rapid and simple colorimetric test for 2,2,2-cryptand (Kryptofix 2.2.2.) in solution

Abstract: A new and versatile method for 2,2,2-cryptand determination in [ 18 F]-labeled radiotracers is described. Proof of concept and applicability of the test method for the commercial radiotracer [ 18 F]-FDG and model compounds FLT and FMISO were also proven.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The techniques used include simple TLC [249][250][251][252], GC [253], HPLC [245,252], and capillary electrophoresis [247], but also highly-sophisticated LC-MS analytics [254]. A novel and simple method makes use of the colour change of I2/Isolutions [255].…”
Section: Advances In Quality Control Proceduresmentioning
confidence: 99%
“…The techniques used include simple TLC [249][250][251][252], GC [253], HPLC [245,252], and capillary electrophoresis [247], but also highly-sophisticated LC-MS analytics [254]. A novel and simple method makes use of the colour change of I2/Isolutions [255].…”
Section: Advances In Quality Control Proceduresmentioning
confidence: 99%
“…Other colorimetric K222 indicator chemistries can likely be used in microfluidic devices as well. Anzellotti et al reported an evaluation of the I 2 /I − indicator for testing PET radiopharmaceuticals and suggested that it could be used to test sample volumes as low as 2–25 µL [ 99 ]. Experiments showed that the color change occurred within 1–2 s, and that the indicator was unaffected by the presence of several salts or amine-containing PET tracers in the formulation.…”
Section: Miniaturization Of Quality Control Testsmentioning
confidence: 99%
“…[ 9–13 ] They are macro‐bicyclic ligands in three forms of exo‐exo , exo‐endo , and endo‐endo [ 14 ] that have high affinity to binding spherical cations. [ 15 ] Recently, Kryptofix 222 has been applied for some pharmaceutical reactions and processes such as dissolving K + salts in nucleophilic [ 18 F]labeled radiotracers, [ 12 ] radium in radiochemical and radiopharmaceutical applications, [ 16 ] and complexation of other metal cations. [ 17 ]…”
Section: Introductionmentioning
confidence: 99%
“…[8] On the other hand, the kryptofix compounds are a specific class of aza-crown ether that is used in supramolecular chemistry materials science, catalysis, separation, and biomedicine. [9][10][11][12][13] They are macro-bicyclic ligands in three forms of exo-exo, exo-endo, and endo-endo [14] that have high affinity to binding spherical cations. [15] Recently, Kryptofix 222 has been applied for some pharmaceutical reactions and processes such as dissolving K + salts in nucleophilic [ 18 F]labeled radiotracers, [12] radium in radiochemical and radiopharmaceutical applications, [16] and complexation of other metal cations.…”
mentioning
confidence: 99%
See 1 more Smart Citation